From Playbuilding to Devising in Literacy Education: Aesthetic and Pedagogical Approaches. Issue 8 (2nd May 2013) - Perry, Mia; Wessels, Anne; Wager, Amanda C.
Abstract The field of literacy education encompasses many different modalities of reading and writing the world, including those of drama, theatre, and performance practiced in both school and community settings. As contemporary theatre practices have broadened performance creation approaches available to literacy and arts educators working with youth and adults, playbuilding and devising offer two modes of creating student‐authored collective performance. Although the processes of playbuilding and devising overlap, they differ in both intention and practice. Both approaches include important frameworks and possibilities for work across literacy education. Following a discussion on the connections between literacy and drama in education, this paper introduces the forms of playbuilding and devising, followed by step‐by‐step illustrations of the practices at work in classrooms. This article, then, acts as an invitation to explore these two vehicles of performance creation in educational and literacy contexts.